Cerebral transmitter precursors and metabolites in advanced renal disease. Issue 7 (July 1978) - Sullivan, P A; Murnaghan, D; Callaghan, N; Kantamaneni, B D; Curzon, G
Abstract : Patients with chronic renal disease had low plasma total tryptophan but an abnormally high proportion of this was in the free state. The subjects with encephalopathy had raised plasma free tryptophan, CSF tryptophan, and CSF 5-hydroxyindoleacetic acid. CSF tryptophan correlated better with plasma free than with plasma total tryptophan. Plasma and CSF tyrosine concentrations were normal but CSF homovanillic acid was raised especially in subjects with encephalopathy. The possible significance of these changes in advanced renal disease is discussed.